Comparison Technology of Wind Speed and Direction Anemometer for Wind Turbines Based on Doppler Lidar - Zhang, Hua; Xing, Tao; Liu, Minghui; Meng, Xianmin; Zhao, Bin (International Journal of Computer Science and Information Technology, 2024)
This paper focuses on the importance of sensors in wind turbines and the limitations of the current calibration method. It introduces a new technology based on Doppler lidar combined with numerical simulation to achieve in-situ and real-time calibration of the wind speed and direction sensor. The technology aims to evaluate the sensor’s working status, quantify the influence of impeller interference, and improve the power generation efficiency of the unit. The key is to use numerical simulation modeling for direct comparison and evaluation. The research contents include quantifying the interference factors of the wind speed and direction sensor using numerical simulation and researching the use of Doppler lidar for sensor calibration. This technology offers advantages such as efficient status evaluation, in-depth result analysis, and reduced unit downtime, filling the technical gap in the wind power industry.